家族性高コレステロール血症における複数種のHMG-CoA還元酵素阻害薬併用効果 - 野末 剛; 井沢 朗; 加藤 文彦; 長沢 晋哉; 野路 善博; 川尻 剛照; 藤堂 康宏; 野原 淳; 稲津 明広; 梶波 康二; 小泉 順二; 馬渕 宏 (動脈硬化 = The journal of Japan Atherosclerosis Society, 2000)
The levels of total and LDL-cholesterol are important risk factors for coronary atherosclerosis and recent clinical trials have shown that LDL-cholesterol lowering is benefical in both the primary and the secondary prevention of CAD. HMG-CoA reductase inhibitor is a potent drug reducing LDL-cholesterol levels, but sufficient reduction of LDL-cholesterol could not be always achieved using its currently recommended dosage in Japan. Accordingly, we studied the efficacy and safety of combined therapy using two kinds of HMGCoA reductase inhibitors, pravastatin and simvastatin, in 20patients (men/women=16/4, mean age 54 years) with heterozygous familial hypercholesterolemia whose LDLcholesterol was more than 160mg/dl and had a coronary atherosclerosis. Three patients had been treated by HMG-CoA reductase inhibitor alone, 3 patients by HMG-CoA reductase inhibitor and bezafibrate, 13 patients by HMG-CoA reductase inhibitor and cholestyramine, 1 patient by HMG-CoA reductase inhibitor and LDL-apheresis. In 12 patients, 5mg/day of simvastatin was added to 20mg/day of pravastatin (simvastatin group). By contrast, in 8 patients, 10mg/day pravastatin was added to 10mg/day of simvastatin (pravastatin group).Mean levels of total cholesterol significantly decreased from 272±44mg/dl (mean±SD) at week 0 to 244±35mg/dl (-10%) at week 12. Mean levels of LDL-cholesterol also significantly decreased from 196±40mg/dl at week 0 to 166±30mg/dl (-15%) at week 12. The mean % changes of total and LDL-cholesterol were -35% and -45% as compared to baseline values, respectively. Decrease of trygliceride levels and increase of HDL-cholesterol levels did not reach statistical significance. Mean levels of apolipoprotein B significantly decreased from 165±32mg/dl at week 0 to 146±27mg/dl (-12%) at week 12, but apolipoproteinsA I and E showed no significant alterations. In pravastatin group, mean levels of LDL-cholesterol decreased from 204±54 at week 0 to 179±39mg/dl (-12%) at week 12. Mean levels of LDL-cholesterol decreased from 202±29 to 159±20mg/dl (-21%) in simvastatin group. There were no difference in mean % changes of total cholesterol, LDL-cholesterol, HDL-cholesterol, and triglyceride between pravastatin group and simvastatin group. During whole study period, there were no adverse events including elevation of CPK, liver injury, and renal dysfunction. We concluded that combined therapy using two kinds of HMG-CoA reductase inhibitors is useful and safe to achieve significant further reduction of LDL-cholesterol in heterozygous familial hypercholesterolemia.